Sculpture Biennale II : Ein-Hod : 1992 : Nature has Built Us a Museum. - Sculpture Biennale Ein-Hod 1992 (Ein-Hod : Biennal of Sculpture, 1992)
Katz, Ruth ; Livne, Doron ; Mounicou, Virginie ; Mezach, David ; Simion-Fainaru, Belu ; Pe'er, David ; Feldman, Dorit ; Primor, Sigal ; Preminger, Alon ; etc.
Sculpture Biennale II : Ein-Hod : 1992 : Nature has Built Us a Museum, , 1992
boek